MODEL MANAJEMEN SUMBERDAYA LOKAL BERBASIS ECOPRENEUR DI KABUPATEN BIMA - Jasman Jasman; Arman Arman (Jurnal Ilmu Administrasi Negara, 2022)
Bima Regency is one of the regencies in West Nusa Tenggara Province that has abundant natural resource potential, but the utilization of these natural resources is still not optimal and many people still live in poverty. Therefore, this research aims to develop an ecopreneurship-based local resource management model in Bima Regency. The research method used was qualitative research with data collection techniques through in-depth interviews and field observations. The results showed that Bima Regency has abundant natural resource potential, such as agriculture, fisheries, and tourism. However, there are still obstacles in the utilization of these natural resources, such as lack of market access and limited technology. The results also show that the concept of ecopreneurship can be an alternative for community empowerment and sustainable economic development in Bima Regency. Through this concept, the community can utilize natural resources sustainably by producing value-added and environmentally friendly products. The ecopreneurship-based local resource management model developed in this study covers four main aspects, namely product and service development, financial management, human resource development, and marketing.